Can carbon risk restrain corporate financialization? Evidence from China - Wang, Yiqiu; Xu, Yang; Guo, Chong; Xie, Meng (Frontiers in Environmental Science, 2024)
Using data on Chinese A-share listed companies from 2010 to 2021, we employ the difference-indifferences (DID) estimation method as an exogenous impact of a quasi-natural experiment and analyze the effects of carbon risk on corporate financialization. We observe that increased carbon risk decreases with corporate financialization, which is more pronounced for financially constrained and state-owned enterprises. Furthermore, we find that carbon risk increases green innovation, which restrains corporate financialization. Our research not only enriches the relevant influence on carbon risk and corporate financialization but also provides Chinese evidence for the Porter hypothesis.